2021
DOI: 10.22175/mmb.11710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dry-Heat Cookery Method on Volatile Flavor Compound Development and Consumer Evaluation of Six Beef Muscles

Abstract: The objective of this study was to determine the influence of dry-heat cookery on beef flavor development of multiple beef muscles. Beef strip loins, top sirloin butts, paired tenderloins, paired shoulder clods, and chuck rolls were collected from USDA Low Choice carcasses (Small00–Small100 marbling; N = 20). Subprimals were wet aged in the absence of light for 21 d at 0°C to 4°C. Subprimals were fabricated into 2.54-cm-thick steaks representative of the following muscles: Gluteus medius, Infraspinatus, Longis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Although the number of unbranded products available to the consumer has greatly decreased in the last decade (Kelly, 2016), the price of the unbranded products is sometimes the only cue available to the consumer. Previous studies have indicated price as the most important trait considered by consumers purchasing steaks and ground beef at retail (Lucherk et al, 2016;Wilfong et al, 2016a;Vierck et al, 2018;Olson et al, 2019;Prill et al, 2019;Vierck et al, 2021). Consistent with those studies, consumers in the current study also identified price as being an important trait when purchasing ground beef.…”
Section: Price Impactsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the number of unbranded products available to the consumer has greatly decreased in the last decade (Kelly, 2016), the price of the unbranded products is sometimes the only cue available to the consumer. Previous studies have indicated price as the most important trait considered by consumers purchasing steaks and ground beef at retail (Lucherk et al, 2016;Wilfong et al, 2016a;Vierck et al, 2018;Olson et al, 2019;Prill et al, 2019;Vierck et al, 2021). Consistent with those studies, consumers in the current study also identified price as being an important trait when purchasing ground beef.…”
Section: Price Impactsupporting
confidence: 86%
“…Increasing the price of more palatable food products often shifts consumers' demands to lower-priced, less palatable food (Cabanac, 1995). Previous work has shown price as the most important motivator considered by consumers when purchasing beef products (Wilfong et al, 2016a;Vierck et al, 2018;Olson et al, 2019;Vierck et al, 2021). In the last decade, the price of ground beef has risen from $5.02 per kilogram in January 2010 to $9.25 per kilogram in April of 2022 (US Bureau of Labor Statistics, 2020).…”
Section: Introductionmentioning
confidence: 99%